2020
DOI: 10.3390/v12030325
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus B3 Infection of Human Neural Progenitor Cells Results in Distinct Expression Patterns of Innate Immune Genes

Abstract: Coxsackievirus B3 (CVB3), a member of Picornaviridae family, is an important human pathogen that causes a wide range of diseases, including myocarditis, pancreatitis, and meningitis. Although CVB3 has been well demonstrated to target murine neural progenitor cells (NPCs), gene expression profiles of CVB3-infected human NPCs (hNPCs) has not been fully explored. To characterize the molecular signatures and complexity of CVB3-mediated host cellular responses in hNPCs, we performed QuantSeq 3′ mRNA sequencing. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Previous studies of acute enteroviral infection showed that: (a) cultured neural cells infected with CBV3 had enhanced secretion of IL6, IL8, and MCP1 and the upregulation of SOCS3, a suppressor of cytokine signaling [ 26 ]; (b) human pancreatic islets infected with CVB3 and CVB4 secreted high amounts of IL6, IL8, MIP-alpha and -beta, and TNF; (c) human pancreatic beta cells infected with CBV4 showed the activation of innate immune pathways including the expression of IFN (alpha, beta, lambda), IL6, IL8, and IL27 and also showed a defective insulin response to glucose [ 35 ]; (d) patients with hand-foot-and-mouth disease caused by EV-A71 and EV-A6 had significantly increased serum levels of IL5, IL7, IL13, IL16, IL18, IP10, NGF-beta, PDGF-beta, and TGFB1 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of acute enteroviral infection showed that: (a) cultured neural cells infected with CBV3 had enhanced secretion of IL6, IL8, and MCP1 and the upregulation of SOCS3, a suppressor of cytokine signaling [ 26 ]; (b) human pancreatic islets infected with CVB3 and CVB4 secreted high amounts of IL6, IL8, MIP-alpha and -beta, and TNF; (c) human pancreatic beta cells infected with CBV4 showed the activation of innate immune pathways including the expression of IFN (alpha, beta, lambda), IL6, IL8, and IL27 and also showed a defective insulin response to glucose [ 35 ]; (d) patients with hand-foot-and-mouth disease caused by EV-A71 and EV-A6 had significantly increased serum levels of IL5, IL7, IL13, IL16, IL18, IP10, NGF-beta, PDGF-beta, and TGFB1 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…CBV3 was used as a reference strain for transcriptome analysis since this virus is pancreotropic and diabetogenic in mice [ 20 , 21 , 22 ] and supported by serologic studies in humans [ 23 ] as well as by the investigation of some T1D cases [ 24 ]. Regarding transcriptome analysis, CBV3 was chosen since complete data have been published on the cellular and transcriptome consequences of CBV3 infection in human cells [ 25 , 26 ]. For acute infection, confluent cultures in T25 flasks were infected at a multiplicity of infection of 3 using 1 mL of virus diluted in cell culture medium and incubated on a rocking platform at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The goal of this article is not to disprove QuantSeq's capability of producing useful results. A demonstration of its utility can be found in Oh et al (2020) which found that the levels of expression of various cytokines correlated with changes in gene expression found using QuantSeq. As with all methods though, we advise care is taken and validation is performed before any conclusions are reached.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated using Direct-zol RNA mini Prep Kit (Zymo Research, Germany) following manufacturer's instructions. RNA sequencing was performed using an Illumina HiSeq 2500 sequencer (Illumina, San Diego, CA) as previously described [18,23,24]. Sequence reads were aligned to the reference genome (Gene bank accession no.…”
Section: Rna Sequencing and Bioinformatics Analysismentioning
confidence: 99%